Use of Human Lung Tissue Models for Screening of Drugs against SARS-CoV-2 Infection - Alexander J. McAuley; Petrus Jansen van Vuren; Muzaffar-Ur-Rehman Mohammed; Faheem; Sarah Goldie; Shane Riddell; Nathan J. Gödde; Ian K. Styles; Matthew P. Bruce; Simran Chahal; Stephanie Keating; Kim R. Blasdell; et al. (Viruses, 2022)
The repurposing of licenced drugs for use against COVID-19 is one of the most rapid ways to develop new and alternative therapeutic options to manage the ongoing pandemic. Given circa 7817 licenced compounds available from Compounds Australia that can be screened, this paper demonstrates the utility of commercially available ex vivo/3D airway and alveolar tissue models. These models are a closer representation of in vivo studies than in vitro models, but retain the benefits of rapid in vitro screening for drug efficacy. We demonstrate that several existing drugs appear to show anti-SARS-CoV-2 activity against both SARS-CoV-2 Delta and Omicron Variants of Concern in the airway model. In particular, fluvoxamine, as well as aprepitant, everolimus, and sirolimus, has virus reduction efficacy comparable to the current standard of care (remdesivir, molnupiravir, nirmatrelvir). Whilst these results are encouraging, further testing and efficacy studies are required before clinical use can be considered.